DESCRIPTION OF IDEAS DURING A DELUSION OCCUR IN A SCHIZOPHRENIA PATIENT - Maria Terok; Esrom Kanine; Tinneke A. Tololiu (Jurnal Ilmiah Perawat Manado (Juiperdo), 2022)
Background:. Background: A schizophrenic with delusions has unrealistic beliefs and dangerous delusional ideas. Purposive: This research aims to identify ideas when delusions occur in schizophrenia patients. The method used is a literature review, a comprehensive summary of several research studies determined by theme. Literature search using the Google Scholar database.Research methods : Literature Review. This research uses case studies, qualitative phenomenological studies, descriptive qualitative, normative law, cross-sectional and case reports taken from articles published from 2016 to 2020.Results and analysis: researchers found 6 articles that were appropriate and met the inclusion criteria for describing ideas when delusions occur in schizophrenic patients, namely having a magical item or tool, having supernatural powers or abilities, experiencing possession or being possessed by a creature, having a high position, feeling frightened by a creature, feeling empty or hollow in the heart, feeling hurt or physically harmed, fasting or certain rituals, feeling like receiving magic/witchcraft from other people, meeting supernatural beings, thinking that other people feel jealous/envy, feeling like they are going to be killed , feels physically disabled/damaged, claims to be God and is controlled by God. As for the aggressive ideas that arise, such as injuring other people, injuring themselves or having suicidal ideas when their delusions occur, even schizophrenic patients when delusions occur in the form of delusions of being chased have ideas about killing because they feel excessively suspicious and feel like they are being chased. Keywords: Schizophrenia, Paranoid Schizophrenia, Delusions.